From SMOG to Fog: A security perspective. - Ríos-del-Pozo, Rubén; Román-Castro, Rodrigo; Onieva-González, José Antonio (IEEE, 2017)
Cloud computing has some major limitations that hinder its application to some specific scenarios (e.g., Industrial IoT and remote surgery) where there are particularly stringent requirements, such as extremely low latency. Fog computing is a specialization of the Cloud that promises to overcome the aforementioned limitations by bringing the Cloud closer to end-users. Despite its potential benefits, Fog Computing is still a developing paradigm which demands further research, especially on security and privacy aspects. This is precisely the focus of this paper: to make evident the urgent need for security mechanisms in Fog computing, as well as to present a research strategy that is being undertaken within the SMOG project, in order to enable a trustworthy and resilient Fog ecosystem.
Keywords: Informática en la nube; Cloud computing; Edge computing; Mobile communication; Ecosystems; Servers; Authentication